Cadres’ role in Posyandu revitalization as stunting early detection in Babakan Madang Sub-District, Bogor District - Rahmawati, Nurul Dina; Sartika, Ratu Ayu Dewi (UI Scholars Hub, 2020)
Stunting, the inability to reach one's full potential, still remains common in Indonesia. As a result of stunting’s intergenerational consequences, many strategies have been conducted by both government and non-government organizations to tackle this issue, including nutrition-specific and sensitive interventions, with Integrated Health Service Post (Posyandu) revitalization as one of the key measures to provide valid, reliable, and up-to-date data to establish the early detection and management of stunting. Unfortunately, this role is sub-optimally performed due to the limited competence of the health volunteers (cadres) that correlates with the suppressed parents’ motivation to visit a Posyandu. Moreover, their difficulties are exaggerated by the weak reporting and supervising system. This study aimed to evaluate the cadres’ knowledge and practice change after a sequence of training to revitalize the Posyandu’s role. This quasi-experimental study involved treatment and control villages located in Babakan Madang Sub-District, Bogor District, from which 41 and 37 cadres participated, respectively: between August and November 2019. The treatment group received three consecutive months of structured training, which comprised different learning methods, namely, group discussions, role plays, games, and seminars about Posyandu and stunting management, maternal and child health, and nutritional assessment. The control group was only visited for observational activities. Changes in cadres’ knowledge and practices were collected using structured quantitative questionnaires and analysed using the Wilcoxon test. Both groups shared a considerably similar practice of Posyandu management, but a significant improvement in cadres’ knowledge was found in the intervention group after the training (p < 0.001) compared with the control group. Longer duration is needed to observe any behaviour change, as indicated by their practice of Posyandu management.